Răspuns :
x³+3x-1 < [x³+3x] ≤ x³+3x (*)
x-1 < [x] ≤ x|³ => (x-1)³ < [x]³ ≤ x³ (**)
x-1 < [x] ≤ x => 3(x-1) < 3[x] ≤ 3x (***)
Adunăm (**) cu (***):
=> (x-1)³+3(x-1) < [x]³+3[x] ≤ x³+3x (****)
Împărțim (*) la (****):
=> (x³+3x-1)/((x-1)³+3(x-1)) < [x³+3x]/([x]^3+3[x]) ≤ (x³+3x)/(x³+3x)
=> (x³+3x-1)/((x-1)³+3(x-1)) < [x³+3x]/([x]^3+3[x]) ≤ 1
Trecem la limită:
=> lim x -> ꝏ (x³+3x-1)/((x-1)³+3(x-1)) < lim x -> ꝏ [x³+3x]/([x]^3+3[x]) ≤ 1
=> 1 < lim x -> ꝏ [x³+3x]/([x]^3+3[x]) ≤ 1
Din criteriul cleștelui:
=> lim x -> ꝏ [x³+3x]/([x]^3+3[x]) = 1
Răspuns:
Explicație pas cu pas:
ptx∈N
avem lim((x³+3x)/(x³+3x))=1
fie x= n+a , a∈(0,1)
x³-1<[x³]<[x³+3x]≤x³+3x
x³-1<[x]³ <[x]³+3[x]<x³+3x
im ((x³-1)/(x³+3x)=1<limita respectiva <lim (x³+3x)/(x³-1))=1
cf.teoremei clestelui, limita este 1 si in acest caz